Resistin -420C>G Promoter Variant and Colorectal Cancer Risk. Issue 3 (July 2014) - Mahmoudi, Touraj; Karimi, Khatoon; Arkani, Maral; Farahani, Hamid; Vahedi, Mohsen; Dabiri, Reza; Nobakht, Hossein; Asadi, Asadollah; Mirakhorli, Mojgan; Arshi, Benafsheh; Derakhshan, Arash; Zali, Mohammad Reza
Purposes: Obesity is associated with an increased risk of colorectal cancer (CRC), and ghrelin (GHRL) and resistin (RETN) are thought to be related to obesity. Our aim was to investigate whether GHRL and RETN gene variants are associated with CRC risk. Materials and Methods: All 414 subjects, including 197 cases with CRC and 217 controls, were genotyped for the GHRL (rs26802) and RETN (rs1862513) or -420C>G gene variants using the PCR-RFLP method. Results: Our findings indicated that the RETN -420C>G "CC" genotype, compared with the "GG" and "GC" genotypes, was a marker of decreased CRC susceptibility; the difference remained significant after adjustment for age, BMI, gender, smoking status, NSAID use, and family history of CRC (p=0.020; OR=0.52, 95% CI=0.30-0.90). Furthermore, after adjustment for confounding factors, the -420C>G "CC" genotype, compared with the "GG" genotype, was associated with a decreased risk for CRC (p=0.044; OR=0.53, 95% CI=0.29-0.98). In addition, no significant difference was observed for the GHRL (rs26802) gene variant. Conclusions: To our knowledge, this is the first study suggesting that the RETN -420C>G "CC" genotype is a marker of decreased CRC susceptibility. This observation is relevant from a scientific perspective and deserves further investigations.